Discursos do sagrado: o uso estratégico da linguagem em práticas do candomblé - Oliveira, Cristina Nascimento de (2012)
This study refers to the Discourse Analysis built in ritual practices of initiation into the Candomblé in a religious house Mina Jeje-Nagô called Ilê Axè Obá D’Alaguinã in Boa Vista, Roraima. Oriented by the theoretical assumptions of Semiolinguistic, the research seeks to establish a reference framework of the constituent elements of Candomblé, its symbolic system, initiation and construction of the sacred processes to understand the dynamics of the discourse in a historically oral tradition religion. Data collecting started in 2009, with weekly visits to the Candomblé meeting place (terreiro) in order to monitor several initiation rituals, establishing a network of contacts essential for the fieldwork. It was also possible the observation in loco of an initiation ritual into Candomblé in 2010 to understand the dynamic operation of that religion, thus realizing that the sacred is constituted in the ritual practices, adding the religious community where discourses are made. Three novices in Candomblé as well as the religious leaders of the Ilê Axè Obá D’Alaguinã and of the terreiro (meeting place) where it was originated – Abassá Afro-Brazilian Lego Xapanã – in Belém, state of Pará were interviewed. Such investigative assumptions concern about the genealogy of these traditional communities of Candomblé meeting place and of its discursive practices, understanding that the oral tradition of Candomblé express itself and is preserved in the religious initiation ceremonies, in a circularity that is not exhausted or extinguished. In this way, it is noticed that the discourse of Mãe Adansan Yatylyssalefan meets the response in her spiritual children, which legitimate it in the researched religious community.